Animal models of bipolar mania: The past, present and future. (3rd May 2016) - Logan, R.W.; McClung, C.A.
Highlights: Pharmacological approaches to induce hyperactivity as a model of human mania have been used for many years. Environmental manipulations are used to induce manic-like states which mimic multiple facets of this complex disorder. Most recent studies have focused on genetic models. Certain outbred strains of mice may be useful in modeling the polygenic nature of this disease. Ultimately, models that cycle through various mood states are needed. Abstract: Bipolar disorder (BD) is the sixth leading cause of disability in the world according to the World Health Organization and affects nearly six million (∼2.5% of the population) adults in the United State alone each year. BD is primarily characterized by mood cycling of depressive (e.g., helplessness, reduced energy and activity, and anhedonia) and manic (e.g., increased energy and hyperactivity, reduced need for sleep, impulsivity, reduced anxiety and depression), episodes. The following review describes several animal models of bipolar mania with a focus on more recent findings using genetically modified mice, including several with the potential of investigating the mechanisms underlying 'mood' cycling (or behavioral switching in rodents). We discuss whether each of these models satisfy criteria of validity (i.e., face, predictive, and construct), while highlighting their strengths and limitations. Animal models are helping to address critical questions related to pathophysiology of bipolar mania, in an effort to more clearly define necessary targets of first-line medications, lithium and valproic acid, and to discover novel mechanisms with the hope of developing more effective therapeutics. Future studies will leverage new technologies and strategies for integrating animal and human data to reveal important insights into the etiology, pathophysiology, and treatment of BD.